Pengaruh Pandemi Covid-19 Pada Niat Kolaborasi Horizontal Logistik Klaster UMKM Di Indonesia - Gita Partiwi; Yuliani Dwi Lestari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
In recent years, horizontal collaboration in logistics is believed to positively impact business performance by reducing cost and increasing fulfillment rates. However, the implementation of horizontal collaborative logistics in MSME clusters in Indonesia still scarce. This research aims to determine the factors that affect the acceptance of industrial clusters to determine the possibility of implementing the concept of collaborative logistics. By combining equality of benefits, competences equity, leadership, trust, competition, cluster’s roles, perceived benefits, and COVID-19 pandemic, a conceptual framework for studying the influencing factors of cooperation intentions is proposed. Partial least squares path modeling (PLS-PM) was conducted on 102 respondents (31 pilots and 71 full research) from business owners or operation managers of six MSME clusters. The results show that the role of trust and clusters has significantly promoted MSME's intention to carry out horizontal logistics collaboration. In addition, the changing business conditions caused by the COVID-19 pandemic proved to be one of the influencing factors. Keywords : Horizontal Collaboration, Logistic, MSME Cluster, Covid-19